Water as a Probe of the Colloidal Properties of Cement - Ridi, Francesca (Langmuir : the ACS journal of surfaces and colloids, 2018)
Cement is produced by mixing mineral phases based on calcium silicates and aluminates with water. The hydration reaction of the mixture leads to a synthetic material with outstanding properties that can be used as a binder for construction applications. Despite the importance of cement in society, for a long time, the chemical reactions involved in its hydration remained poorly understood as a result of the complexity of hydration processes, nanostructure, and transport phenomena. This feature article reviews the recently obtained results using water as a probe to detail the essential features in the setting process. By examining the peculiar physicochemical properties of water, fundamental information on the evolving inorganic colloid matrix can be deduced, ranging from the fractal nanostructure of the inorganic silicate framework to the transport phenomena inside the developing porosity. A similar approach can be transferred to the investigation of a plethora of other complex systems, where water plays the main role in determining the final structural and transport properties (i.e., biomaterials, hydrogels, and colloids)